LIBERTY AND RESPONSIBILITY AT SELF-REALIZATION OF TEACHING STAFF - Moskovets, Liudmyla (PSYCHOLOGICAL JOURNAL, 2019)
The article presents the key results of the performed theoretical analysis of such phenomena as liberty and responsibility and their importance for teaching staff’s self-realization. Positive and negative liberty is differentiated. The performed theoretical research pays special attention to the ideas of E. Fromm and V. Frankl on the role of liberty for individuation. The essence of autonomy as a notion relevant to liberty and facilitating decision-making in different spheres of human life is defined. The levels, phases, directions and criteria of responsibility development are determined. Internality (internal locus of control) as a notion closely connected to responsibility is interpreted. The article author states that positive liberty manifests itself in conscious activities that involve personal decision-making to overcome obstacles for harmonic revealing of potential abilities based on personal positive values, as well as personal activity restrictions and limitations. Consequently, all this will facilitate and promote self-realization. Liberty can be a driving force for personal activities and provides capabilities to resolve different individual controversies and to prove personal maturity. The following interlink of liberty and responsibility as the philosophic and psychological categories was defined: liberty without responsibility is converted into high-handedness, while responsibility, in its turn, is connected with making willed decisions by an individual and finding the ways to implement them. The following contribution into the determination of the role and place of liberty and responsibility in personal self-realization was made: the first category is a structural element of the activity component manifested in deeds and decisions, while the second one is the condition ensuring successful realization of person’s positive nature and character features. The role of liberty and responsibility in teaching staff’s self-realization process is studied. Freedom of choice provides the elderly pedagogues with great opportunity to move towards their self-realization. They can take their own decisions whether to continue their professional work or to turn to another activities such as public, socially beneficial, volunteering efforts, etc.